Magnetic Circular Dichroism of Porphyrin Lanthanide M3+ Complexes. Issue 10 (13th August 2014) - Andrushchenko, Valery; Padula, Daniele; Zhivotova, Elena; Yamamoto, Shigeki; Bouř, Petr
ABSTRACT Lanthanide complexes exhibit interesting spectroscopic properties yielding many applications as imaging probes, natural chirality amplifiers, and therapeutic agents. However, many properties are not fully understood yet. Therefore, we applied magnetic circular dichroism (MCD) spectroscopy, which provides enhanced information about the underlying electronic structure to a series of lanthanide compounds. The metals in the M3+ state included Y, La, Eu, Tb, Dy, Ho, Er, Tm, Yb, and Lu; the spectra were collected for selected tetraphenylporphin (TPP) and octaethylporphin (OEP) complexes in chloroform. While the MCD and UV‐VIS absorption spectra were dominated by the porphyrin signal, metal binding significantly modulated them. MCD spectroscopy was found to be better suited to discriminate between various species than absorption spectroscopy alone. The main features and trends in the lanthanide series observed in MCD and absorption spectra of the complexes could be interpreted at the Density Functional Theory (DFT) level, with effective core potentials on metal nuclei. The sum over state (SOS) method was used for simulation of the MCD intensities. The combination of the spectroscopy and quantum‐chemical computations is important for understanding the interactions of the metals with the organic compounds. Chirality 26:655–662, 2014. © 2014 Wiley Periodicals, Inc.